(untitled) (Al-Mansour Journal, 2024)
" Adjective phrase " is one of the areas in grammar that may cause difficulties to learners. So, this study has been designed to investigate students’ ability in dealing with "adjective phrase" and the difficulties that might face in using it. To achieve this goal, 65 undergraduate / second year students / Department of English / College of Basic Education / University of Mosul for the academic year 2022 – 2023 have been chosen randomly. The data are prepared in three procedures which have been planned in three forms: the test, the questionnaire, and the interview. The test includes fifteen sentences containing "adjective phrase" which have been designed by the researcher. The questionnaire includes Yes – No questions, whereas the last form is the interview which took twenty-six days to complete with the sample of study (sixty-five) students. In the light of the results, it has been found that most students at university level own satisfactory awareness of using" adjective phrases" as opposed to others who find difficulties in using them. Such difficulties are found in their inability to identify the adjective phrase in the sentence and put it in a meaningful one. The study is terminated by some recommendations that may enable the students to overcome their difficulty in using adjective phrase.